(3GdfUhU aj JMbjb GdWhQ GdeNUhUs - (3eMeO Hf ESMGb Hf eMeO Hf jhSa Hf Ydj Gdbhfhj GdQhej, UOQ GdOjf,J (B673 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CHGf eQGJH Yde Gdjbjf hYjfg hMbg hOQLGJg s
(3BNQgG (B:s
(3hLhOoG ESJhMOG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B30s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1956s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds